P-024 Preliminary experience with the percutaneous embolization of juvenile angiofibromas (JNAs) using only ethylene vinyl alcohol copolymer (EVOH) Onyx. (12th July 2011) - Gemmete, J; Chaudhary, N; Pandey, A; Marentette, L; McKean, E; Sullivan, S
Abstract : Background: JNAs are hypervascular tumors that may benefit from pre-operative devascularization to reduce intra-operative blood loss. The optimal method for devascularization of these tumors is not known. Methods: A consecutive series of seven JNAs were treated with percutaneous embolization with EVOH as the sole embolic agent. 1—Fischer Type I, 1—Fischer Type II, 4—Fischer type IIIb, and 1 Fischer Type IVa tumors were treated. Results: Complete devascularization of the seven JNAs was achieved in all cases percutaneously with only EVOH. There were no complications. The average intraoperative blood loss was 680 ml (range 10–1700 ml). Three of the type IIIb tumors were completely removed from only an endoscopic approach. Conclusions: Our preliminary experience suggests that EVOH may offer a higher degree of devascularization when compared with other embolic agents. This may facilitate an easier surgical resection with lower blood loss. EVOH seems to be safe when percutaneously injected as the sole embolic agent into a JNA.